Respostas
respondido por:
2
Boa tarde
( (n + 1)! - n! ) / (n - 1)! = 8n
( n + 1)*n! - n!) = 8n*(n - 1)!
( n!*(n + 1 - 1) ) = 8n*(n - 1)!
n!*n = 8n*(n - 1)!
n! = 8*(n - 1)!
n*(n - 1)! = 8*(n - 1)!
n = 8
( (n + 1)! - n! ) / (n - 1)! = 8n
( n + 1)*n! - n!) = 8n*(n - 1)!
( n!*(n + 1 - 1) ) = 8n*(n - 1)!
n!*n = 8n*(n - 1)!
n! = 8*(n - 1)!
n*(n - 1)! = 8*(n - 1)!
n = 8
respondido por:
2
Vamos desenvolver os fatoriais ...
(n+1)! - n! /(n-1)! = 8n
(n+1).n.(n-1)! - n.(n-1)!/(n-1)! = 8n (costo todos (n-1)! )
(n+1).n - n = 8n
n² + n - n = 8n
n² = 8n
n² - 8n = 0 fatorando ...
n.(n-8) = 0
n' = 0 é um resultado ...
n - 8 = 0
n'' = 8 outro resultado .
Resposta:
n = 0 ou n = 8 . ok
(n+1)! - n! /(n-1)! = 8n
(n+1).n.(n-1)! - n.(n-1)!/(n-1)! = 8n (costo todos (n-1)! )
(n+1).n - n = 8n
n² + n - n = 8n
n² = 8n
n² - 8n = 0 fatorando ...
n.(n-8) = 0
n' = 0 é um resultado ...
n - 8 = 0
n'' = 8 outro resultado .
Resposta:
n = 0 ou n = 8 . ok
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás